Advances in apical microsurgery: Technique, materials and prognosis - Azuma, Mariane M. [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Valentim, Diego [UNESP]; Gomes Filho, João Eduardo [UNESP]; Dezan Junior, Eloi [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2015)
Primary endodontic treatment for teeth with apical periodontitis is a generally reliable and successful procedure where the objective of treatment is to eliminate intraradicular infection. However, the prognosis of retreatment cases involving a periapical lesion may be poorerarticularly when a procedural error has occurred, which increases the difficulty to eliminate bacteria from the canal. Apical microsurgery is an important treatment modality for treating apical periodontitis (AP) that persists even performing orthograde root canal treatment. The goals of apical surgery are removal of diseased periapical tissues and sealing of apical root canal system to facilitate regeneration of hard and soft tissues, including the formation of new attachment cells. Over the years, many studies have provided extensive data regarding the prognosis of apical surgery performed using a variety of root-end filling materials and surgical techniques. According to the literature, the use of high-power illumination and magnification (microscope or endoscope), ultrasonic tips for root-end cavity preparation, micro-instruments, and mineral trioxide aggregate (MTA) for root-end filling produces significantly better results than those of traditional root-end surgery. Thus, the aim of this dissertation is to discuss the techniques and materials that can employed to increase the success rates of apical microsurgery.